2011
DOI: 10.1890/09-0896.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of a boreal forest to canopy opening: assessing vertical and lateral tree growth with multi-temporal lidar data

Abstract: Fine-scale height-growth response of boreal trees to canopy openings is difficult to measure from the ground, and there are important limitations in using stereophotogrammetry in defining gaps and determining individual crowns and height. However, precise knowledge on height growth response to different openings is critical for refining partial harvesting techniques. In this study, we question whether conifers and hardwoods respond equally in terms of sapling growth or lateral growth to openings. We also ask t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 86 publications
3
65
0
Order By: Relevance
“…Stereo optical imagery or laser scanning data have tremendous potential for obtaining area-wide three-dimensional data over several thousands of hectares. Their usage in the analysis of forested areas over an entire country opens up new possibilities for biomass estimations [2,3], forest structure analysis [4,5], biodiversity assessment [6,7] and the optimization of forest inventories at a national level [8].…”
Section: Introductionmentioning
confidence: 99%
“…Stereo optical imagery or laser scanning data have tremendous potential for obtaining area-wide three-dimensional data over several thousands of hectares. Their usage in the analysis of forested areas over an entire country opens up new possibilities for biomass estimations [2,3], forest structure analysis [4,5], biodiversity assessment [6,7] and the optimization of forest inventories at a national level [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ease with which data can be updated allows us to readjust the estimations and quickly assess changes or disturbances in forest stands by estimating their development over time, or establish comparisons between different areas with a simple update of the forestry cartography (Riaño et al, 2004). The bibliography contains numerous studies that used bi-temporal data from two LiDAR flights to estimate plant growth (Yu et al, 2004(Yu et al, , 2006Naesset & Gobakken, 2005;Hopkinson et al, 2008;Vepakomma et al, 2011;Fekety et al, 2014;Cao et al, 2016;Song et al, 2016). Some researchers have estimated the growth of trees in forests on the basis of the differences in height derived from LiDAR data in flights separated by a 2-yr interval (Naesset & Gobakken, 2005;Yu et al, 2006;Vepakomma et al, 2011;Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The bibliography contains numerous studies that used bi-temporal data from two LiDAR flights to estimate plant growth (Yu et al, 2004(Yu et al, , 2006Naesset & Gobakken, 2005;Hopkinson et al, 2008;Vepakomma et al, 2011;Fekety et al, 2014;Cao et al, 2016;Song et al, 2016). Some researchers have estimated the growth of trees in forests on the basis of the differences in height derived from LiDAR data in flights separated by a 2-yr interval (Naesset & Gobakken, 2005;Yu et al, 2006;Vepakomma et al, 2011;Cao et al, 2016). These studies allowed the growth in different forestry parameters to be calculated, such as the basal area or volume (Naesset & Gobakken, 2005) as well as estimations of the vertical and lateral growth of trees (Vepakomma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicators extracted from the so-called Canopy Volume Profile approach (CVP) were found to be more closely related to several of the conventional forest parameters. Similar voxel-based approaches were also successfully used to retrieve forest parameters at stand, plot and tree levels using total frequency of discrete return sampling along height bins of canopy columns [23,[30][31][32]. Generally speaking, [33] indicated that structural parameters that combine height and gap fraction, i.e., the fraction of open sky not obstructed by canopy elements [34], improve biomass estimations.…”
Section: Introductionmentioning
confidence: 99%